Alloy and manufacturing method thereof

By forming an interference film with a nano -level oxidation layer of less than 200 nanometer on the surface of the gold alloy, it solves the problem that the oxidation color of gold alloy in existing technology is difficult to achieve a variety of colors. The allergenic problem of oxidant.

CN119372520APending Publication Date: 2025-01-28CHOW SANG SANG JEWELRY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410997511.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-26
Filing Date
2024-07-24
Publication Date
2025-01-28

Smart Images

  • Figure CN119372520A_ABST
    Figure CN119372520A_ABST
Patent Text Reader

Abstract

The invention provides an alloy and a manufacturing method thereof. The alloy is provided with an interference film. In one embodiment, the alloy consists essentially of 55.0% to 78.0% by weight of Au, 8.0% to 24.0% by weight of Ag, 8.0% to 24.0% by weight of Cu, and 0.0% to 3.0% by weight of a deoxidizer; the interference film is grown directly from the inside of the alloy to one surface of the alloy and has a thickness of less than 200 nanometers; the interference film is characterized in that the interference film presents a surface color.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to surface colors on gold alloys. Background Art

[0002] In jewelry manufacturing, precious metals of different colors can be combined to create beautiful and desirable products. Traditionally, gold alloys come in a variety of colors, with yellow, white, and rose gold being the most common. Different colors can be created by varying the ratio of silver to copper in the composition of the gold-silver-copper alloy. New colors can also be brought to gold alloys by implementing surface treatments such as electroplating and oxidation coloring.

[0003] Oxidation is a process that creates a thin colored layer on the surface of a metal, usually bronze and copper, by oxidation. Patinas of copper and bronze, whether natural or artificial, are usually bluish-green. Oxidation is generally used as a method to provide a protective coating to metals, but in the jewelry industry, it is more commonly used as a technique for coloring jewelry alloys. The color of the surface of an oxidized metal alloy depends on the composition of the metal alloy and the heat treatment method used. For example, a jewelry alloy containing chromium may appear red after heat treatment due to the formation of Cr(VI) oxides, while a jewelry alloy containing iron may appear green after heat treatment due to the formation of iron(II) oxides.

[0004] European Patent No. EP0438980 discloses forming a black cobalt oxide layer on a cobalt-containing gold alloy (Au-Ag-Cu-Co) by heat treatment at 400°C to 1100°C for 15 minutes to one hour. However, the application of cobalt is limited by its high ease of oxidation. The use of a high percentage (3-5%) of cobalt is not conducive to investment casting due to excessive oxidation and high melting point. Investment casting is very important in the jewelry manufacturing industry because it can produce high-precision surface treatments and provide a high degree of flexibility in product design. The inability to perform investment casting will cause many difficulties in the manufacturing process. In addition, the alloy can only obtain a black oxide.

[0005] Likewise, Japanese Patent No. JP2185934 discloses that gold alloys (Au-Mn-Fe, Au-Mn-Co, and Au-Ag-Mn-Fe) with a brown surface can be obtained by heat treatment at 850° C. to 900° C. for 2 minutes. Since manganese, iron, and cobalt are all very easily oxidized, using high percentages (5-40%, respectively) of manganese, iron, and cobalt in jewelry investment casting will cause problems.

[0006] US Patent No. 5,059,255 discloses a gold alloy (Au-Fe-Ni) that exhibits a blue color after heat treatment at 450°C to 600°C for 10-12 minutes. As is well known, nickel is a common cause of skin allergies. Therefore, nickel is avoided in new jewelry alloy inventions.

[0007] The present invention uses a gold alloy with only copper and silver added, which is free of toxic substances and allergens. This alloy can be easily produced by investment casting without the disadvantages caused by oxidation. Unlike the above inventions, the present invention can create a series of predetermined coloring effects for the same gold alloy. This will provide diverse opportunities and benefits to the jewelry manufacturing and design industries.

[0008] The difference between the present invention and the existing gold alloy oxidation coloring technology must be emphasized. In the present invention, a wide range of multiple colors can be produced by controlling the heating time, while other gold alloy oxidation coloring processes can only produce one or two colors. The most significant difference is the source of the oxidation color. The oxidation color in the prior art comes from the metal oxide layer of several microns thick, and the oxidation color depends on the color of the metal oxide. However, in the present invention, the surface color comes from the thin film interference of the nanometer-level oxide layer. Summary of the invention

[0009] The present invention provides an alloy with an interference film. In one embodiment, the alloy is substantially composed of 55.0-78.0wt% Au, 8.0-24.0wt% Ag, 8.0-24.0wt% Cu and 0.0-3.0wt% deoxidizer; the interference film is grown on a surface of the alloy and has a thickness of less than 200 nanometers; and the interference film exhibits a surface color.

[0010] The present invention provides an alloy having an interference film. In one embodiment, the alloy is substantially composed of 55.0-78.0wt% Au, 8.0-24.0wt% Ag, 8.0-24.0wt% Cu and 0.0-3.0wt% deoxidizer; the interference film is directly grown from the alloy onto a surface of the alloy and has a thickness of less than 200 nanometers; the interference film exhibits a predetermined surface color.

[0011] The present invention also provides a decorative article comprising the alloy of the present invention.

[0012] The present invention further provides a method for preparing an alloy having an interference film. In one embodiment, the method comprises the following steps: (a) providing the alloy consisting essentially of 55.0-78.0 wt% Au, 8.0-24.0 wt% Ag and 8.0-24.0 wt% Cu and 0.0-3.0 wt% deoxidizer; the alloy comprises a surface for forming the interference film; and (b) heating the alloy to a temperature of 400 to 500° C. for a period of time in an inert environment to form the interference film on the surface; the thickness of the interference film is less than 200 nanometers and exhibits a surface color.

[0013] The present invention further provides a method for preparing an alloy having an interference film, the method comprising the following steps: (a) providing the alloy basically consisting of 55.0-78.0wt% Au, 8.0-24.0wt% Ag and 8.0-24.0wt% Cu and 0.0-3.0wt% deoxidizer; the alloy includes a surface for forming the interference film; and (b) heating the alloy to a temperature of 400 to 500°C in an inert environment for a period of time to allow the interference film to grow directly from the alloy onto a surface of the alloy; the thickness of the interference film is less than 200 nanometers and exhibits a predetermined surface color. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1A It is an overall representation diagram of the present invention.

[0015] Figure 1B It is an overall representation diagram of the pre-processing in one embodiment of the present invention.

[0016] Figure 2 This is a FESEM image magnified 80,000 times, showing that the purple surface color layer is no thicker than 200 nanometers. The cross section was polished by ion beam milling.

[0017] Figure 3 This is a FESEM image magnified 100,000 times, showing that the blue surface color layer is no thicker than 200 nanometers. The cross section was polished by ion beam milling. DETAILED DESCRIPTION

[0018] The following terms will be used to describe the present invention. In the absence of specific definitions herein, the terms used to describe the present invention should be interpreted according to their common meanings understood by those of ordinary skill in the art.

[0019] As used herein, the expression "BSE" refers to backscattered electrons.

[0020] In this document, the expression "FESEM" refers to field emission scanning electron microscopy.

[0021] An object of the present invention is to provide a method for coloring a gold alloy.

[0022] Another object of the present invention is to provide a method for coloring gold alloys made using conventional alloys and conventional processes, including but not limited to investment casting.

[0023] Another object of the present invention is to provide a method for coloring a gold alloy, wherein the resulting colors include, but are not limited to, orange, red, purple, blue, green, yellow, etc. The surface color can be measured by a three-dimensional color measurement system CIELAB coordinates. The L* axis is defined as black at 0 and white at 100 to measure lightness, the a* axis is defined as red at a positive value and green at a negative value to measure red and green components, and the b* axis is defined as yellow at a positive value and blue at a negative value to measure yellow and blue components.

[0024] The present invention provides a method of inducing coloration on a gold alloy. In one embodiment, the gold alloy consists essentially of 55.0 to 78.0 wt % Au; 8.0 to 24.0 wt % Ag; and 8.0 to 24.0 wt % Cu.

[0025] In one embodiment, the gold alloy may substantially include no more than 3.0 wt % of a deoxidizer to replace Ag and Cu.

[0026] In one embodiment, the deoxidizer is selected from Zn or Si or a mixture thereof.

[0027] In one embodiment, the gold alloy consists essentially of 55.0 to 62 wt % Au; 17.0 to 24.0 wt % Ag and 17.0 to 24.0 wt % Cu.

[0028] In one embodiment, the gold alloy consists essentially of 72.0 to 78.0 wt % Au; 8.0 to 17.0 wt % Ag; and 8.0 to 17.0 wt % Cu.

[0029] In one embodiment, the gold alloy consists essentially of 56.8 to 59.8 wt % Au; 19.3 to 22.4 wt % Ag; and 19.3 to 22.4 wt % Cu.

[0030] In one embodiment, the gold alloy consists essentially of 73.5 to 76.5 wt % Au; 11.0 to 14.0 wt % Ag; and 11.0 to 14.0 wt % Cu.

[0031] In one embodiment, the gold alloy consists essentially of 58.3 wt % Au; 20.85 wt % Ag; and 20.85 wt % Cu.

[0032] In one embodiment, the gold alloy consists essentially of 75.0 wt % Au; 12.5 wt % Ag; and 12.5 wt % Cu.

[0033] In one embodiment, the present invention provides a method for preparing a gold alloy having a predetermined color characteristic. The overall representation of the method is shown in FIG. Figure 1AIn one embodiment, the method further comprises: Figure 1B The method of the present invention may include the following steps: melting gold, silver, copper and a selectively added deoxidizer and pouring them into a mold of a predetermined shape to form an alloy; etching the alloy; polishing the alloy; heating the alloy to 400° C. to 800° C. in air for the first time until a gray-black color visible to the naked eye appears; cooling the alloy to room temperature; etching the alloy for a second time; polishing the alloy; heating the alloy to 400° C. to 500° C. in an inert environment for a second time; and cooling the alloy to room temperature in air.

[0034] In one embodiment, the alloy is prepared by conventional investment casting techniques.

[0035] In one embodiment, the alloy is etched by dilute acid.

[0036] In one embodiment, the dilute acid is dilute sulfuric acid or dilute hydrochloric acid.

[0037] In one embodiment, the portion of the surface of the alloy to be colored is polished to a mirror finish.

[0038] In one embodiment, the alloy is first heat treated at a furnace temperature between 400 and 800° C. for at least 10 minutes in a normal atmospheric environment, such as ordinary air. The alloy will have a gray-black surface and then be cooled to room temperature.

[0039] In one embodiment, the alloy is subjected to a second heat treatment in an inert environment at a furnace temperature between 400° C. and 500° C. When the alloy cools to room temperature, a color change of the polished surface is observed.

[0040] In one embodiment, the inert environment is argon.

[0041] In one embodiment, the surface color of the alloy depends on the duration of the second heat treatment.

[0042] In one embodiment, the color difference (ΔE) of the surface layer formed before and after the second heat treatment step is at least 10.0.

[0043] In one embodiment, the surface color of the alloy includes, but is not limited to, orange, red, purple, blue, green to yellow.

[0044] In one embodiment, the surface color of the polished surface of the alloy is uniform.

[0045] In one embodiment, the thickness of the surface color layer does not exceed 200 nanometers. Figure 2 and Figure 3BSE FESEM image showing a typical cross section of an oxide colored gold alloy according to one embodiment of the present invention, with a surface color layer thickness of less than 200 nanometers.

[0046] In one embodiment, if the existing oxidation color on the alloy needs to be changed, the alloy can be etched, polished and heat treated again in an inert environment at 400° C. to 500° C. The duration of the heat treatment can be adjusted according to the corresponding color specified by the previous second heat treatment.

[0047] The present invention provides an alloy with an interference film. In one embodiment, the alloy is substantially composed of 55.0-78.0wt% Au, 8.0-24.0wt% Ag, 8.0-24.0wt% Cu and 0.0-3.0wt% deoxidizer; the interference film is grown on a surface of the alloy and has a thickness of less than 200 nanometers; and the interference film exhibits a surface color.

[0048] The present invention provides an alloy having an interference film. In one embodiment, the alloy is substantially composed of 55.0-78.0wt% Au, 8.0-24.0wt% Ag, 8.0-24.0wt% Cu and 0.0-3.0wt% deoxidizer; the interference film is directly grown from the alloy onto a surface of the alloy and has a thickness of less than 200 nanometers; the interference film exhibits a predetermined surface color.

[0049] In one embodiment, the surface color includes orange, red, purple, blue, green or yellow.

[0050] In one embodiment, the predetermined surface color includes orange, red, purple, blue, green or yellow.

[0051] In one embodiment, the surface layer has a color difference (ΔE) of at least 10.0 compared to the unoxidized surface.

[0052] In one embodiment, the predetermined surface color has a color difference (ΔE) of at least 10.0 compared to the unoxidized surface.

[0053] In one embodiment, the alloy consists essentially of: i) 55.0 to 62 wt% Au; 17.0 to 24.0 wt% Ag and 17.0 to 24.0 wt% Cu; ii) 72.0 to 78.0 wt% Au; 8.0 to 17.0 wt% Ag and 8.0 to 17.0 wt% Cu; iii) 56.8 to 59.8 wt% Au; 19.3 to 22.4 wt% Ag and 19.3 to 22.4 wt% Cu; iv) 73.5 to 76.5 wt% Au; 11.0 to 14.0 wt% Ag and 11.0 to 14.0 wt% Cu; v) 58.3 wt% Au; 20.85 wt% Ag and 20.85 wt% Cu; or vi) 75.0 wt% Au; 12.5 wt% Ag and 12.5 wt% Cu.

[0054] In one embodiment, the oxygen scavenger includes one or more of zinc or silicon.

[0055] In one embodiment, the alloy is formed by investment casting.

[0056] The present invention also provides a decorative article comprising the alloy of the present invention.

[0057] In one embodiment, the ornament is a piece of jewelry.

[0058] The present invention further provides a method for preparing an alloy having an interference film. In one embodiment, the method comprises the following steps: (a) providing the alloy consisting essentially of 55.0-78.0 wt% Au, 8.0-24.0 wt% Ag and 8.0-24.0 wt% Cu and 0.0-3.0 wt% deoxidizer; the alloy comprises a surface for forming the interference film; and (b) heating the alloy to a temperature of 400 to 500° C. for a period of time in an inert environment to form the interference film on the surface; the thickness of the interference film is less than 200 nanometers and exhibits a surface color.

[0059] The present invention further provides a method for preparing an alloy having an interference film. In one embodiment, the method comprises the following steps: (a) providing the alloy consisting essentially of 55.0-78.0wt% Au, 8.0-24.0wt% Ag and 8.0-24.0wt% Cu and 0.0-3.0wt% deoxidizer; the alloy comprises a surface for forming the interference film; and (b) heating the alloy to a temperature of 400 to 500°C in an inert environment for a period of time to allow the interference film to grow directly from the alloy onto a surface of the alloy; the thickness of the interference film is less than 200 nanometers and exhibits a predetermined surface color.

[0060] In one embodiment, the method further comprises pre-treating the surface of the alloy in step (a) before step (b).

[0061] In one embodiment, the pre-treatment comprises the steps of: (i) heating the alloy to 400 to 800° C. in air; and (ii) etching and polishing the surface.

[0062] In one embodiment, step (i) comprises heating the alloy for at least 10 minutes or until a grey-black or black coloration is observed.

[0063] In one embodiment, the surface layer is orange, red, purple, blue, green or yellow in color.

[0064] In one embodiment, the color caused by the interference film is orange, red, purple, blue, green or yellow.

[0065] In one embodiment, the interference film causes the surface to have a color difference (ΔE) of at least 10.0 compared to before.

[0066] In one embodiment, the inert environment is argon.

[0067] In one embodiment, the method further comprises forming the alloy in step (a) by investment casting prior to step (b).

[0068] In one embodiment, the method further comprises repeating step (b) to change the color of the surface layer until a predetermined color is obtained.

[0069] In one embodiment, the method further comprises etching and polishing the surface of the alloy before repeating step (b).

[0070] In one embodiment, the period of time is controlled based on one or more parameters including the size of the surface, the size of the alloy, or the temperature of step (b).

[0071] In one embodiment, the period of time will be shortened when the temperature of step (b) is higher.

[0072] The present invention will be better understood through the following examples, but those skilled in the art will readily appreciate that the specific examples described in detail are only illustrative and are not meant to limit the invention described herein, which will be defined by the following claims.

[0073] In this application, various references or publications are cited. In order to more fully describe the state of the art to which the present invention relates, the disclosures of these references or publications are hereby fully incorporated into this application. It should be noted that the transitional term "comprising", "including", "containing" or "characterized by" is inclusive or open, and does not exclude additional, unmentioned elements or method steps.

[0074] Example 1

[0075] A 6 gram gold alloy ring was prepared according to the method of the present invention, and its composition was 75.0 wt% Au, 12.5 wt% Ag, 12.5 wt% Cu. The alloy was cast, etched with dilute sulfuric acid and polished. After the first heating at 500°C in air for 15 minutes, the oxidized alloy showed a gray-black coloration. The CIELAB coordinates of the alloy at this stage were as follows: L*42.61, a*-0.35, b*-1.58. The alloy was then etched and polished again with dilute sulfuric acid. The CIELAB coordinates of the polished surface of the alloy were measured (Test 1), and the results are shown in Table 1. The alloy was heated for a second time at 450°C in argon for 2 minutes and cooled to room temperature in air. The polished surface of the alloy showed a red surface color, as shown in the CIELAB measurement results in the following table (Test 2). The alloy was etched, polished, and heated again at 450°C in argon for four times with different durations. It can be seen that different heating durations on the same alloy will lead to different surface colors (Tests 3 to 6).

[0076] Tests 7 to 9 compare different alloys consisting of 75.0 wt% Au, 12.5 wt% Ag and 12.5 wt% Cu. The heat treatment conditions and CIELAB measurement results of the resulting alloy surfaces are shown in Table 1 below. Comparison of the CIELAB results of Tests 7, 8 and 5 indicates that the first heat treatment step of heating at 500°C for 15 minutes in air is necessary to achieve the desired surface color. Comparison of the CIELAB results of Tests 9 and 5 indicates that an inert environment must be maintained in the second heat treatment step of heating at 450°C for 5 minutes to obtain a bright and attractive color on the alloy. Table 1. Experimental results

[0077] Example 2

[0078] Two 6-gram gold alloys were prepared according to the method of the present invention and compared, and their compositions are listed in Table 2. These alloys were cast, etched with dilute sulfuric acid, and polished. After the first heat treatment step of heating at 500°C for 15 minutes in air, the CIELAB coordinates of Tests 10 and 11 were L*49.91, a*-0.44, b*0.76 and L*57.10, a*-2.08, b*5.60, respectively. These alloys were etched with dilute sulfuric acid and polished before the second heat treatment. The CIELAB coordinates before and after the second heat treatment step of heating at 450°C for 5 minutes in argon are listed in Table 2. The result of Test 10 was a brown color that did not achieve the intended effect. ΔE is a measure that quantifies the difference between two colors, where any value below 2 is barely detectable by the human eye. The ΔE of the CIELAB results of Test 11 measured before and after the second heat treatment was only 1.54, indicating that the intended surface color was not formed. Comparison of the CIELAB results for Runs 5 (Table 1), 10 and 11 (Table 2) shows that alloy compositions deviating from the specific embodiments of the present invention will not result in the intended surface color. Table 2. Experimental results

Claims

1. An alloy having an interference film, characterized in that: i. The alloy consists essentially of 55.0-78.0wt% Au, 8.0-24.0wt% Ag, 8.0-24.0wt% Cu and 0.0-3.0wt% deoxidizer; ii. The interference film is grown directly from the alloy onto a surface of the alloy and the interference film has a thickness of less than 200 nanometers; The feature of the invention is that the interference film presents a predetermined surface color.

2. The alloy according to claim 1, characterized in that: The predetermined surface color includes orange, red, purple, blue, green or yellow.

3. The alloy according to claim 1, characterized in that: The predetermined surface color has a color difference (ΔE) of at least 10.0 compared to the unoxidized surface.

4. The alloy according to claim 1, characterized in that: The alloy basically comprises: i. 55.0 to 62 wt% Au; 17.0 to 24.0 wt% Ag and 17.0 to 24.0 wt% Cu; ii. 72.0 to 78.0 wt% Au; 8.0 to 17.0 wt% Ag and 8.0 to 17.0 wt% Cu; iii. 56.8 to 59.8 wt% Au; 19.3 to 22.4 wt% Ag and 19.3 to 22.4 wt% Cu; iv. 73.5 to 76.5 wt% Au; 11.0 to 14.0 wt% Ag and 11.0 to 14.0 wt% Cu; v.58.3wt%Au;20.85wt%Ag and 20.85Cu; vi. 75.0 wt% Au; 12.5 wt% Ag and 12.5 wt% Cu.

5. The alloy according to claim 1, characterized in that: The deoxidizer includes one or more of zinc or silicon.

6. The alloy according to claim 1, characterized in that: The alloy is formed by investment casting.

7. A decorative item, characterized in that: The decorative article comprises the alloy according to claim 1.

8. The decorative article according to claim 7, characterized in that: The ornament is a piece of jewelry.

9. A method for preparing an alloy having an interference film, characterized in that: The method comprises the following steps: a. providing an alloy consisting essentially of 55.0-78.0wt% Au, 8.0-24.0wt% Ag and 8.0-24.0wt% Cu and 0.0-3.0wt% deoxidizer; said alloy comprising a surface for forming said interference film; and b. heating the alloy to a temperature of 400 to 500°C in an inert environment for a period of time to allow the interference film to grow directly from the alloy to a surface of the alloy; the thickness of the interference film is less than 200 nanometers and exhibits a predetermined surface color.

10. The method according to claim 9, further comprising pre-treating the surface of the alloy in step (a) before step (b).

11. The method according to claim 10, characterized in that: The pre-processing comprises the following steps: i. heating the alloy to 400 to 800°C in air; and ii. Etching and polishing the surface.

12. The method according to claim 11, characterized in that: The step (i) comprises heating the alloy for at least 10 minutes or until a grey-black or black coloration is observed.

13. The method according to claim 9, characterized in that: The color of the interference film is orange, red, purple, blue, green or yellow.

14. The method according to claim 9, characterized in that: The interference film has a color difference (ΔE) of at least 10.0 compared to the unoxidized surface.

15. The method according to claim 9, characterized in that: The inert environment is argon.

16. The method of claim 9, further comprising forming the alloy in step (a) by investment casting prior to step (b).

17. The method according to claim 9, further comprising repeating step (b) to change the color of the surface layer until a predetermined color is obtained.

18. The method of claim 17, further comprising etching and polishing the surface of the alloy before repeating step (b).

19. The method according to claim 9, characterized in that: The period of time is controlled based on one or more parameters including the size of the surface, the size of the alloy, or the temperature of step (b).

20. The method according to claim 19, characterized in that: When the temperature of step (b) is higher, the period of time will be shortened.

Citation Information

Patent Citations

  • Cobalt-containing precious metal material for decoration and process for preparing the same

    EP0438980A1

  • Coloring a gold alloy

    US5059255A